2019
DOI: 10.1128/jvi.01818-18
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Infection in Human Dipeptidyl Peptidase 4-Transgenic Mice Infected with Middle East Respiratory Syndrome Coronavirus

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) infection can manifest as a mild illness, acute respiratory distress, organ failure, or death. Several animal models have been established to study disease pathogenesis and to develop vaccines and therapeutic agents. Here, we developed transgenic (Tg) mice on a C57BL/6 background; these mice expressed human CD26/dipeptidyl peptidase 4 (hDPP4), a functional receptor for MERS-CoV, under the control of an endogenous hDPP4 promoter. We then characterized this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 54 publications
2
43
0
Order By: Relevance
“…Similar to the model by Agrawal et al, activated innate immune cells accumulated in the lungs after MERS-CoV infection. Recently, Yoshikawa et al observed the cytokine storm in a newly generated hDPP4-transgenic mouse [37].…”
Section: Mouse Expressing Human Receptormentioning
confidence: 99%
“…Similar to the model by Agrawal et al, activated innate immune cells accumulated in the lungs after MERS-CoV infection. Recently, Yoshikawa et al observed the cytokine storm in a newly generated hDPP4-transgenic mouse [37].…”
Section: Mouse Expressing Human Receptormentioning
confidence: 99%
“…MERS-CoV does not replicate in wild-type mice because of differences in the receptor binding domain of DPP4 (31)(32)(33). To overcome this, many groups, including ours, have developed transgenic mice that express human DPP4 (34)(35)(36)(37)(38)(39). In our model, exons 2-25 of mouse DPP4 were replaced with the human DPP4 sequence (DPP4 H/M ) (34).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that transgenic mice expressing the human DPP4 (hDPP4) receptor could be infected intranasally with MERS-CoV and developed acute pneumonia. [13][14][15] Therefore, hDPP4 transgenic mice were selected for exposure to MERS-CoV-containing aerosols using an animal nose-only exposure device.…”
Section: Introductionmentioning
confidence: 99%